Thermodynamics of As, Sb and Bi distribution during reverb furnace smelting - Mitevska N.; Živković Živan D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The results of thermodynamic analysis of arsenic, antimony and bismuth distribution between copper matte and discard slag in reverberatory smelting at 1573 K are shown in this paper. On the basis of chemical analysis of the melt samples taken during stable operation of the reverb furnace No.2 in the Copper Smelter and Refinery, RTB Bor (Yugoslavia), the distribution coefficients of As, Sb, and Bi between copper matte and slag are calculated. The influence of the matte grade on the minor element distribution coefficients between copper matte and slag is also analyzed, as well as arsenic, antimony and bismuth distribution in slag.